PERFORMANCE COMPARISON OF PT. XYZ PLANTATION FROM FINANCIAL AND NON-FINANCIAL ASPECTS USING BALANCED SCORECARD - Harahap, Adhi Surya (Politeknik Negeri Medan, 2024)
One indicator of the financial performance of the Return On Investment and Return On Equity in PT Perkebunan XYZ tend to be experiencing a decline, but this does not automatically indicate the condition of the company are not optimal. The values ​​of the financial ratios only indicate financial performance so that there is a tendency to ignore this aspect of non-financial, such as customer satisfaction, productivity, and cost-effectiveness process used to produce products and services, and empowerment, and employee commitment to delivering products and services for customer satisfaction. Performance measurement that takes into account the financial aspects and non-financial aspects are balanced scorecard still maintaining the traditional financial measures. The purpose of this study which analyzes the performance of PT Perkebunan XYZ comprehensive and can serve as the basis for long-term planning and to recommend steps that need to be done by the management of PT Perkebunan XYZ, so that the measurement results Balanced Socrecard can be implemented in improving company performance by considering four perspectives . The results showed that the first perspective learning and growth perspective shows an increase in the number of employees who attend training and development, increasing the ratio of the load of training and development as well as increased capital organization proven to increase customer satisfaction and employee motivation. In the perspective of both the internal business processes perspective shows PT Perkebunan XYZ able to create quality products. The third perspective which shows the customer perspective customers are satisfied with the quality of services provided by the company. Net profits are seen fluctuations, the average profit per customer and profitability per customer increased, while average operating expenses per customer declined. The fourth perspective of the financial perspective showed increased growth in revenue and net profit margin however decreased ROI.